KAJIAN STILE PADA NOVEL RONGGENG DUKUH PARUK DAN BEKISAR MERAH KARYA AHMAD TOHARI - Syaripah; Asep Saepurokhman; Kuswara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on stylistic analysis in two novels by Ahmad Tohari: Ronggeng Dukuh Paruk and Bekisar Merah. These two novels were chosen because of Tohari's distinctive depiction of rural social realities, poverty, and the struggles of life, expressed through his unique style. The study of style in these two novels is crucial to uncovering how Ahmad Tohari utilizes the power of language to construct a fictional world rich with meaning and value. In addition to strengthening appreciation for modern Indonesian literature, this research is also beneficial for developing literature learning in schools, particularly in developing students' critical thinking skills and empathy for social realities through the interpretation of literary language. This study aims to identify, classify, and analyze the style used by the author in the novels Ronggeng Dukuh Paruk and Bekisar Merah, relating to symbolism, sociocultural realities, and the elements that shape the stories. The research method used is descriptive qualitative with a stylistic approach. Data were obtained through in-depth reading of the novel texts, followed by recording and categorizing stylistic elements. Data analysis was conducted by interpreting how these language choices shape meaning, create atmosphere, and deepen characterization. The theoretical framework used refers to stylistic concepts developed by experts, which distinguish between everyday language and literary language. The results of the study indicate that Ahmad Tohari utilizes a rich and nuanced style. In Ronggeng Dukuh Paruk, there is a strong use of local diction (Banyumasan dialect), personification that brings nature to life, and sharp imagery to depict poverty and suffering. The language used often feels poetic and flowing, reflecting local wisdom and tradition. Meanwhile, in Bekisar Merah, the style tends to be more reflective and psychological. The diction chosen emphasizes descriptions of the characters' inner states, with metaphors and similes depicting internal conflicts. The conclusion of this study confirms that style in Ahmad Tohari's works functions not merely as ornamentation, but as an integral element that builds the narrative, reinforces the theme, and reflects the author's worldview on social reality.